The first report of Naobranchia cygniformis Hesse, 1863 (Copepoda: Lernaeopodidae) off South Africa, with a redescription of the adult female. - Dippenaar, S. & M. Sebone (African Journal of Marine Science, 2021)
Naobranchia cygniformis Hesse, 1863 is one of 21 accepted species of the genus Naobranchia, which is distinguished from other genera in the family Lernaeopodidae by the possession of ribbon-like maxillae. The original description of N. cygniformis lacked detail concerning the armature, and later reports have not included a redescription. Thus, a redescription with details regarding the armature will be valuable for future comparative purposes. Additionally, this report of this parasitic copepod on the seabream Pagellus natalensis from the east coast of South Africa constitutes a new host and geographic record, since the only other Naobranchia species reported from the Indian Ocean off South Africa are N. kabatana and N. pritchardae.